Coimmobilization of enzymes in bilayers using pei as a glue to reuse the most stable enzyme: Preventing pei release during inactivated enzyme desorption. (October 2017) - Zaak, Hadjer; Kornecki, Jakub F.; Siar, El-Hocine; Fernandez-Lopez, Laura; Corberán, V. Cortés; Sassi, Mohamed; Fernandez-Lafuente, Roberto
Graphical abstract: Highlights: Octyl-lipase coated with PEI may be used to co-immobilize lipases and galactosidase. Desorption of the second enzyme by incubation at high ionic strength release also PEI. Use of glyoxyl-octyl and modification of lipase with glutaraldehyde reduce the PEI release. OC-GLX-TLL and LU modified with GLU and PEI can be reused after galactosidase desorption without loss of PEI for several cycles. Abstract: Coimmobilization of enzymes using polyethylenimine (PEI) as glue permits to reuse the most stable enzyme, immobilized on the support, after its incubation at high ionic strength to desorb the other enzyme, immobilized via ion exchange. However, this produced PEI desorption. Now, we solve this problem via covalent immobilization of the PEI on the immobilized first and more stable enzyme and the glyoxyl support. The phospholipase Lecitase ultra (LU) and the lipase from Thermomyces lanuginosus (TLL) have been immobilized in octyl (OC) and OC-glyoxyl (OC-GLX) agarose beads, coated with PEI and used to immobilize β-galactosidase from Aspergillus oryze . The treatment of immobilized lipases with glutaraldehyde and the use of glyoxyl-octyl allowed preventing PEI release, even in the presence of 6 M NaCl. As covalently immobilized LU and TLL were more stable than β-galactosidase, 3 cycles of β-galactosidase adsorption, thermal inactivation, desorption by incubation in 6 M NaCl and reloading of a fresh batch of galactosidase batch were performed. During these treatments, LU retained around 90% of the activity and TLL more than 80%, and the PEI bound to these biocatalysts was maintained. This new strategy probed to be useful to allowing reusing the most stable enzyme without any further treatment.